UPAYA PEMECAHAN KETIMPANGAN PERSEBARAN PENDUDUK DALAM RANGKA MEMPERCEPAT PEMBANGUNAN DAERAH - I Ketut Sudibia (PIRAMIDA, 2005)
Imbalance of population distribution in Indonesia, especially between Java and outside Java actually has been emerged since Dutch Colonization. At that period Dutch Colonizer has tried to overcome the problem through Colonization program, and after the independent period this program was continued by the so called Transmigration program. However, it seems that this program was not so successfully implemented. It was reflected by development of population distribution between Java and outside Java was not greatly changing for four decades. Based on 1961 Population Cencus result, Java with 6,9 percent of the widht of Indonesian archipelago recided by 65,0 percent of Indonesian population. Additionally, 2000 Population Cencus result shows that it change slightly become 60,1 percent. The low achievement of transmigration program in that period, based on the analysis of several experts, is caused by some following restrictions, 1) centris demography orientation, 2) lack of integration, 3) unclear measuring rod, 4) lack of coordinaion among related transmigration institutions, and 5) the lack of cultural approach. At the regional autonomy era, the approach of development planning arrangement is bottom-upvoriented, which is sign regional freedom for setting its own development in accordance with the needs and condition of each region. It is just the same as population mobility program, which previously is being oriented toward supply side, in the regional autonomy era is more to be oriented toward demand side of receiver. Through this needs approach, the place of receiver has to be able to identify qualification, composition, and amount of labor force needed. The need of labor force related to regional development of destination place can be done by following steps, 1) collaboration in research related to potencial of place of destination, 2) establishment of public utilities and infrastructures at the place of destination, 3) dissemination of project establishment at the place of destination to migrant candidate at the place of origin, 4) collaboration in migrant selection process, 5) collaboration in education and training for migrant candidate, 6) collaboration in departure cost and cost of living in the certain period, 7) collaboration related to skill needed for development in the palce of destination, 8) market availability, and 9) availability of safety guarrantee at the palce of destination. With this kind of mobility system, it can both overcome imbalance of population distribution and accelerate regional development.